Determinantes de la salud que se asocian a los factores de riesgo en los trabajadores de la Finca Eden Roses de Cayambe - Tuquerres Cachiguango, Ronny Raúl (2024)
People who work in the flower sector are exposed to various threats that are harmful to their health, such as exposure to chemicals, biological contaminants, physical and mental burdens, unsafe environmental conditions, and unhealthy lifestyles. These factors affect the quality of life and health status of workers in this sector. Therefore, the objective of the study was to describe the health determinants associated with risk factors in the workers of the “Eden Roses” farm in Cayambe. This research was based on a descriptive methodology with a quantitative and transversal approach. 100 floricultural cultivation and harvesting laborers were selected as the study population, while the sample was made up of 81 workers, which was obtained through intentional probabilistic sampling. Prior to this process, socialization of the study and informed consent were carried out. As a result of the research carried out at the 'Eden Roses' Farm, it is highlighted that the main determinant of health is lifestyle and lifestyle habits. The majority of workers disciplinedly comply with the farm's rules and protocols, demonstrating a notable commitment to their health and work safety. In addition, health determinants associated with existing risk factors in the work environment of this sector were identified, such as being exposed to chemical substances, especially pesticides and pesticides used in flower production, in addition to poor ergonomics related to postures and repetitive movements. Also in question No. 9 we consider the result since 75% of the population reports that as a result of working in the flower sector they have developed skin, respiratory and MSD diseases. It is suggested to continue with more detailed research on the repercussions of working in the field of floriculture to ensure the health of flower growers. Furthermore, it is recommended to develop more evaluation models or tools specifically designed for this sector as a preventive and health promotion measure.